COLLAGEN EXTRACTION OF PATIN FISH SKIN (Pangasius sp.) WITH DIFFERENT PAPAIN ENZYMES CONCENTRATION - Bunga M.W Bunga M.W; Rahman Karnila; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract This study aims to determine the effect of different papain enzyme concentrations on collagen extraction from the skin of catfish (Pangasius sp.). The method used was an experimental method with completely randomized concoctions (CRD). The treatments given consisted of E0 (Control), E1 (5% papain enzyme), E2 (10% papain enzyme), E3 (15% papain enzyme). This research consisted of 3 stages, namely 1) preparation of raw catfish, 2) deproteination of catfish skin, 3) hydrolysis of raw catfish with acetic acid.The parameters tested were collagen yield, proximate analysis (moisture content, ash content, and protein content), pH, and functional group (FTIR). The results showed that the quality of the collagen obtained increased along with the increase in the concentration of the enzymes used. This is presumably because the addition of the enzyme concentration in the collagen extraction process will increase the yield produced because the enzyme breaks the cross-linking of the collagen telopeptide and dissolves it. Based on this, the use of the optimum concentration was obtained at a concentration of 15% (E2) with a protein content of 71,60%, 14.17%water, and4.21% ash Keywords:Collagen, Catfish, Extraction, Papain Enzymes.